Novel chemical weapon of an exotic macroalga inhibits recruitment of native competitors in the invaded range. (21st December 2012) - Svensson, J. Robin; Nylund, Göran M.; Cervin, Gunnar; Toth, Gunilla B.; Pavia, Henrik; Callaway, Ray
Summary Allelopathy is an important non‐resource interaction in terrestrial plant communities that may affect invasions by non‐indigenous plants. The 'novel weapons hypothesis' (NWH) predicts that non‐indigenous plants will become invasive if they have allelopathic compounds that assemblages in the new range are not adapted to. Recently, the non‐indigenous, chemically rich macroalga Bonnemaisonia hamifera (Hariot) has become one of the most abundant filamentous red algae in Scandinavian waters. We used B. hamifera to specifically test the aspect of the NWH that concerns invasion success based on novel allelochemicals in the invaded range. Allelopathic interactions were tested through effects on the growth rate of adult native macroalgae in co‐cultures with B. hamifera and through the settlement success of native macroalgal propagules and microalgae on surfaces coated with 1, 1, 3, 3‐tetrabromo‐2‐heptanone. We also investigated whether 1, 1, 3, 3‐tetrabromo‐2‐heptanone can be transferred from B. hamifera to its native host algae, as a means of pre‐emptive competition. The settlement of native macroalgal propagules and microalgae was strongly inhibited on surfaces coated with 1, 1, 3, 3‐tetrabromo‐2‐heptanone at ecologically relevant concentrations, but there were no effects of adult B. hamifera on growth rates of adults of the six native naturally co‐occurring species. The compound was shown to be transferred from B. hamifera to the surface of its native host algae at inhibitory concentrations in both laboratory and field experiments. By inhibiting the settlement of propagules on its thallus and on surrounding surfaces, B. hamifera achieves a competitive advantage over native macroalgae, a finding that parallels previous reports on soil‐ and litter‐mediated allelopathic interactions among vascular plants. Because competition for available substrata in marine benthic systems is intense, the ability to reserve space may be vital for B. hamifera's successful invasion. This is the first example of an allelopathic compound that can be transferred by direct contact from an exotic to a native species, with an active and unaltered function. Synthesis. Our results clearly show that the main secondary metabolite of the invasive red alga B. hamifera has strong allelopathic effects towards native competitors, suggesting that its novel chemical weapon is important for the highly successful invasion of new ranges.